2012
DOI: 10.1002/ccd.24483
|View full text |Cite
|
Sign up to set email alerts
|

Approaches for dislodged stent retrieval during transradial percutaneous coronary interventions

Abstract: Transradial percutaneous coronary intervention (PCI) has been associated with a lower incidence of major access site related complications. With the increased implementation of transradial approach in complex PCI, stent dislodgement is unavoidable in any interventionalists' career. Stent retrieval is different in a transradial approach as compared to a transfemoral approach because of the former's smaller arterial size. In this review, we outline the different stent retrieval techniques with considerations fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…We successfully removed the detached microcatheter tip via the guide-extension catheter trapping technique (GeT technique) using a guide-extension catheter and a small balloon. A previous report described the successful percutaneous retrieval of a disrupted balloon catheter using this method [7,8]. However, to the best of our knowledge, this is the first report of successful percutaneous retrieval of a detached microcatheter tip through this method.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…We successfully removed the detached microcatheter tip via the guide-extension catheter trapping technique (GeT technique) using a guide-extension catheter and a small balloon. A previous report described the successful percutaneous retrieval of a disrupted balloon catheter using this method [7,8]. However, to the best of our knowledge, this is the first report of successful percutaneous retrieval of a detached microcatheter tip through this method.…”
Section: Discussionmentioning
confidence: 85%
“…Various methods have been reported for the retrieval of entrapped or broken devices, such as the use of a snare catheter, the twisted guidewire technique, biopsy forceps, the low-pressure balloon inflation technique, and the small-balloon inflation technique [1][2][3][4][5][6][7]. In this case, the use of a snare catheter was unsuitable due to the small size of the detached tip.…”
Section: Discussionmentioning
confidence: 96%
“…Various stent retrieval techniques, including a small-balloon technique and a double-wire technique, and devices, including gooseneck snares, forceps, and baskets, have been described [11,12]. Most cases retrieved unexpanded stents, and these retrieval procedures were often performed via the femoral artery rather than the radial artery.…”
Section: Discussionmentioning
confidence: 98%
“…A search of the PubMed database resulted in only eight cases with a successful experience of PSE through the transradial approach (20). The transradial method employed in the present study was based on common cardiovascular interventional treatment procedures, without a documented increased risk of stroke (21–23). Our data showed that the procedure time and X-ray exposure time were slightly lower by using the radial access as compared to the femoral approach.…”
Section: Discussionmentioning
confidence: 99%